DETERMINING STRESS AND DEFORMATION OF REINFORCED CONCRETE SLABS WITH COMPOSITE LAYERS RESISTANT TO AGGRESSIVE ENVIRONMENTS - Xursanboyev , Temurbek Dilshodbek o‘g‘li (Innovative Development in Educational Activities, 2023)
This article aims to investigate the stress and deformation characteristics of reinforced concrete slabs incorporating composite layers designed to withstand aggressive environmental conditions. Following the IMRAD structure (Introduction, Methods, Results, and Discussion), we explore the experimental assessment of these composite materials and their application in enhancing the durability and performance of reinforced concrete structures exposed to harsh environmental factors. The findings provide valuable insights into the behavior of such composite layers and their potential to mitigate the detrimental effects of aggressive environments on concrete slabs.